George Moore : Influence and Collaboration. - Heilmann, Ann (University of Delaware, 2014)
George Moore: Influence and Collaboration explores in sustained form for the first time the nature of Moore's interactions with other European writers and artists of the fin de siècle. This book explores the full range of Moore's collaborations and cultural encounters: from 1870s Paris art exhibitions to turn-of-the-century Dublin and London.